2008 International Conference on Innovations in Information Technology 2008
DOI: 10.1109/innovations.2008.4781679
|View full text |Cite
|
Sign up to set email alerts
|

The effect of using domain specific ontologies in query expansion in medical field

Abstract: Domain specific ontologies can be used to improve both precision and recall of information retrieval systems. One approach in this regard is using query expansion techniques and the other would be introducing a semantic similarity measure for concepts in ontology. Although each approach has its own benefits and drawbacks, query expansion techniques are preferred when the corpus volume is so huge that examining concept pairs between query and documents is not reasonable. In this paper a semantic query expansion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Mao et al [24] integrated a MeSH-enhanced concept layer into a language modeling framework to capture concept associations. Jalali et al [25] matched concept pairs between queries and documents using a semantic query expansion method. These studies motivate us to optimize query expansion in consideration of domain knowledge.…”
Section: Related Workmentioning
confidence: 99%
“…Mao et al [24] integrated a MeSH-enhanced concept layer into a language modeling framework to capture concept associations. Jalali et al [25] matched concept pairs between queries and documents using a semantic query expansion method. These studies motivate us to optimize query expansion in consideration of domain knowledge.…”
Section: Related Workmentioning
confidence: 99%
“…In biomedicine, QE studies primarily focus on ontologies and pseudo-relevance feedback. For example, Jalali and Borujerdi (2008) and expand queries via MeSH ontology, and Srinivasan (1996), Aronson (1996), and Zhu et al (2006) expand queries via Unified Medical Language System (Lindberg et al, 1993). On the other hand, biomedical queries can be reformulated or systematically expanded based on initially retrieved documents focusing on abbreviations (Bacchin and Melucci, 2005), the controlled vocabulary of MeSH (Thesprasith and Jaruskulchai, 2014), or open vocabulary (Rivas et al, 2014).…”
Section: Related Workmentioning
confidence: 99%
“…Lu et al found that their replication of the PubMed's 4 Automatic Term Mapping (ATM) to MeSH terms was effective in finding more relevant documents, while, it did not improve the precision in the top retrieved documents. Jalali and Borujerdi [24] used the synonyms of the identified MeSH terms or direct descendants of them in the queries as expansion terms, and reported improvement over the various retrieval systems such as expansion with general purpose ontologies.…”
Section: Exploiting Meta-data For Patient Irmentioning
confidence: 99%